2019
DOI: 10.3390/cancers11091217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor and Immunological Heterogeneity on the Anti-Cancer Immune Response

Abstract: Metastatic tumors are the primary cause of cancer-related mortality. In recent years, interest in the immunologic control of malignancy has helped establish escape from immunosurveillance as a critical requirement for incipient metastases. Our improved understanding of the immune system’s interactions with cancer cells has led to major therapeutic advances but has also unraveled a previously unsuspected level of complexity. This review will discuss the vast spatial and functional heterogeneity in the tumor-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 199 publications
(210 reference statements)
0
30
0
Order By: Relevance
“…Overexpression of PRL3 is associated with heightened tumorigenicity and metastatic spread and is thus an attractive immunotherapeutic target (297). Blocking PRL3 with a humanized antibody (PRL3zumab) enriched NK cells in the tumor niche and promoted tumor clearance in mouse models (298). Since this study also demonstrated elevated expression of PRL3 on multiple patientderived tumor samples with little expression on the matched healthy tissue, this therapeutic approach may be beneficial for additional malignancies, and may provide enhanced specificity for immunotherapy.…”
Section: Novel Nk Cell Inhibitory Checkpoints/tumor Antigens For Blocmentioning
confidence: 69%
“…Overexpression of PRL3 is associated with heightened tumorigenicity and metastatic spread and is thus an attractive immunotherapeutic target (297). Blocking PRL3 with a humanized antibody (PRL3zumab) enriched NK cells in the tumor niche and promoted tumor clearance in mouse models (298). Since this study also demonstrated elevated expression of PRL3 on multiple patientderived tumor samples with little expression on the matched healthy tissue, this therapeutic approach may be beneficial for additional malignancies, and may provide enhanced specificity for immunotherapy.…”
Section: Novel Nk Cell Inhibitory Checkpoints/tumor Antigens For Blocmentioning
confidence: 69%
“…Levels of TIM-3, CTLA-4, TIGIT, TOX, TOX2, and SIRT1 genes in tumor tissue were significantly higher than that of the circulation; their expressions within the TME could be induced by tumor-mediated immunosuppression [ 3 , 26 ]. These data implicate the potential importance of their elevated expression in the TME and their potential contribution to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissues are heterogeneous; different tumor types and at various pathological stages can express different levels of inhibitory ICs, transcription factors and other molecules to escape immunosurveillance and promote tumor growth [26]. Therefore, we investigated whether there were any differences in mRNA levels of different genes between early and advanced disease stages (Fig.…”
Section: Comparative Analyses Of Ics and T Cell Exhaustion Markers Inmentioning
confidence: 99%
“…There is a report focusing on the immune function of TECs. Cancer cells can evade immunosurveilance because of the abnormal circumstances caused by the tumor microenvironment [76]. Huang et al studied the α1,3-galactosyltransferase (α1,3 GT) synthesizing carbohydrate epitope Galα1-3Galβ1-4GlcNAc-R on the cell surface, which is a major barrier to xenotransplantation [77].…”
Section: For Targeting Tumor Endothelial Cellsmentioning
confidence: 99%